The output loss during disinflation - Bailey, Martin (Estudios de Economía, 2016)
This paper deals with the output losses associated with periods of restrictive monetary and fiscal policy and of declining rates of inflation. The results using data from several countries for the seventies, tend to support the findings that inflation takes about three years to come down by the number of percentage points of the cutback of monetary expansion. Also it was found that the maximum rate of loss of output comes in the second year after the year of the cutback.